(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
Based on the existence of pullback attractors for the non-autonomous stochastic plate equations with multiplicative noise and nonlinear damping defined in the entire space R^n by Xiaobin Yao in [15], in the paper, we further investigate the upper semicontinuity of pullback attractors for the problem.